2018
DOI: 10.14735/amko2018213
|View full text |Cite
|
Sign up to set email alerts
|

Selected Genetic Polymorphisms Associated with Hypoxia and Multidrug Resistance in Monoclonal Gammopathies Patients

Abstract: Background: Adaptive response to hypoxia is regulated by several mechanisms and transcription factors, includ ing hypoxia-inducible factors (HIFs). Activation of HIF-1α is associated with increased expression of P-glycoprotein and multidrug resistance in cancer cells. In this retrospective study, we analyzed candidate single-nucleotide polymorphisms (SNPs) in HIF-1α and HIF-1β associated with risk of monoclonal gammopathy of undetermined significance (MGUS) or multiple myeloma (MM). Patients and Methods: Genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Rs2057482 is located in 3′UTR of HIF1A. There are several reports that hypothesized that the minor T allele in this polymorphism may decrease the HIF1A expression by creating a new microRNA binding site [ 22 , 51 54 ]. However, according to our data, neither the tumor nor the normal kidney HIF-1α tissue levels did not appear to be influenced by any of these two polymorphisms in HIF1A .…”
Section: Discussionmentioning
confidence: 99%
“…Rs2057482 is located in 3′UTR of HIF1A. There are several reports that hypothesized that the minor T allele in this polymorphism may decrease the HIF1A expression by creating a new microRNA binding site [ 22 , 51 54 ]. However, according to our data, neither the tumor nor the normal kidney HIF-1α tissue levels did not appear to be influenced by any of these two polymorphisms in HIF1A .…”
Section: Discussionmentioning
confidence: 99%
“…The HIF1A gene has many SNPs, but we focused on rs2057482 for the following reasons: First, the relationship between rs2057482 and cancer risk has been reported in previous epidemiology studies [12][13][14][15][16][17][18]. Second, in the 1000 Genomes Project Phase 3, minor allele frequencies of rs2057482 are greater than 10% in most populations (Additional file 1: Table S4).…”
Section: Discussionmentioning
confidence: 99%
“…The rs2057482 polymorphism is located in the 3'UTR of HIF1A. Many researchers have hypothesized that this polymorphism may be located near the microRNA binding site and that it affects the expression of HIF1A by binding HIF1A to the microRNA [13,[15][16][17][18]. Wang et al reported that rs2057482 may affect the expression of HIF1A by microRNA 199a [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation